Digital stories as a tool for health promotion and youth engagement - Fletcher, Sarah (Can J Public Health, 2016)
OBJECTIVES: To provide opportunities for intergenerational knowledge sharing for healthy lifestyles; to facilitate youth and Elder mentorship; and to increase the self-esteem of youth by celebrating identity, cultural practices and community connection through the creation and sharing of digital stories. PARTICIPANTS: A youth research team (8 youth) aged 13–25, youth participants (60 core participants and 1 70 workshop participants) and Elders (14) from First Nations communities. SETTING: The project was conducted with participants from several communities on Vancouver Island through on-site workshops and presentations. INTERVENTION: Youth and Elders were invited to a 3-day digital story workshop consisting of knowledge-sharing sessions by Elders and digital story training by the youth research team. Workshop attendees returned to their communities to develop stories. The group re-convened at the university to create digital stories focused on community connections, family histories and healthy lifestyles. During the following year the research team delivered instructional sessions in communities on the digital story process. OUTCOMES: The youth involved reported increased pride in community as well as new or enhanced relationships with Elders. CONCLUSIONS: The digital stories method facilitated intergenerational interactions and engaged community members in creating a digital representation of healthy lifestyles. The process itself is an intervention, as it affords critical reflection on historical, cultural and spiritual ideas of health and what it means to be healthy in an Aboriginal community. It is a particularly relevant health promotion tool in First Nations communities with strong oral history traditions.